NUTRITIONAL STATUS AND SOME RELATED FACTORS OF CHILDREN WITH ACUTE RESPIRATORY TRACT INFECTIONS AT THUY NGUYEN DISTRICT GENERAL HOSPITAL, HAI PHONG CITY (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the nutritional status and describe some factors related to nutrition in children with respiratory tract infections who were hospitalized at Thuy Nguyen General Hospital in 2024 - 2025.Research method: Cross-sectional descriptive study.Results: Among the 240 children participating in the study, the age group 1-
Keywords: Nutritional status, respiratory infections, malnutrition